Morbidity and Mortality of Premature Birth at Ramadi Teaching Hospital for Maternity and Children/West of Iraq - Sabah M Ali; Rana F Shitran (Acta Medica Iranica)
The consequences of prematurity is a very fundamental subject. With improvement of neonatal care facilities, it still comprises a burden on health care centers, with a lot of costs and increasing mortality. To determine the morbidity and mortality of premature birth at Ramadi teaching hospital for maternity and children. A prospective cohort study was done at Ramadi teaching hospital for maternity and children/Anbar/Iraq. Data was collected from 1st July 2022 till 1st January 2023, all live births at Ramadi Teaching Hospital during that period were included. All admitted premature newborns were followed up in neonatal care unit for variable periods depending on clinical situation and those who develop complications were recorded (Respiratory distress syndrome, Intracranial hemorrhage, asphyxia, sepsis, hypoglycemia, pneumothorax) furthermore any newborn died during hospitalization period also recruited. The total number of neonates was 204. All of them were preterm babies. About 121 (59.3%) need resuscitation while 83 (40.7%) not need resuscitation. Regarding complications respiratory distress syndrome 156(76.5%), intracranial hemorrhage 9(4.4%), asphyxia 17(8.3%), sepsis 35(17.2%), hypoglycemia 22 (10.8%), pneumothorax 31(15.2%). 148 premature babies discharged well (72.5%) while 56 premature newborns died (27.5%). Result of analysis of logistic regression to determine the relationship between different risk factors and mortality shows significant association with birth weight <1500-gram Odd’s ratio (30.041), and triplet pregnancy Odd’s ratio (3.62). Respiratory distress syndrome is the most prevalent complication of preterm babies followed by sepsis. Extremely low birth weight and triplet pregnancy have significant association with preterm mortality